INTEGRATION OF SATELLITE AND TERRESTRIAL COMMUNICATION NETWORKS IN THE CONTEXT OF GLOBAL INTERNET ACCESS - Fedor Shagzheev (American Journals Publishing, 2024)
This article examines the current state of standardization, architectural integration models, and key technical challenges, including spectrum management, high latency variability, and inter-segment roaming. Implementation recommendations and practical scenarios are provided, demonstrating the importance of hybrid networks for universal connectivity.
Keywords: Satellite communications, non-terrestrial networks (NTN), 5G, LEO constellations, global Internet access, network integration, communications redundancy, 3GPP Release 17/18.